Pengembangan Media E-Book untuk Materi Morfem Bebas dan Terikat pada Mata Pelajaran Bahasa Indonesia - Nadia Nadila; Ayu Nafira; Herawati Herawati; Lidia Agnesia Lumban Batu (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
To improve the understanding of fifth grade elementary school students about the material of free morphemes and bound morphemes, this type of research is research and development (R&D). The results of the preliminary study showed that there was no learning media that facilitated learning and that students did not understand free morphemes and bound morphemes. Based on these findings, the author plans to create an illustrated e-book called